ADOPSI INOVASI LALADAKTA DI BIDANG ADMINISTRASI KEPENDUDUKAN DI KABUPATEN ROKAN HULU - Sigit Muamar Yusuf; Zaili Rusli (CV. Adiba Aisha Amira, 2024)
The Laladakta service program is a process of adopting a service innovation launched by the Kecepatan District Government to facilitate population administration services for the community in the Kepuas District area which was adopted from the Melenia Child Puberty Innovation from the Payakumbuh City Population and Civil Registration Service. This research aims to determine and analyze the process of adopting the laladakta innovation carried out by the Kepuas Subdistrict government in collaboration with the Rokan Hulu district population and civil registration service and all village midwives throughout the Kepuas Subdistrict and analyze the inhibiting factors in the process of adopting the laladakta public service innovation program in full district. This research uses qualitative research methods with a descriptive approach. This research refers to Rogers' Innovation Adoption theory which has 5 indicators, namely the knowledge stage, persuasion stage, decision making stage, implementation stage and confirmation stage. The results of this research indicate that the process of adopting innovations in Laladakta population administration services in Kecepatan District has been able to achieve these five processes and is running well as expected. Factors that influence the implementation of innovation are cooperation between intas and good communication and factors that become obstacles in this research are a less than optimal socialization process and a lack of human resources. In this way, the Kecepatan District Government is expected to increase direct outreach to the community by involving all government agencies including the village government and PKK organizations, so that the Laladakta population administration service program runs smoothly.